Effect of sintering on the microstructural and mechanical properties of meleagris gallopova hydroxyapatite - (:unkn) unknown (IOS PRESS, 2014)
In this study, we obtained hydroxyapatite powders from the femur bones of meleagris gallopova at three steps and sintered at five different temperatures. The reactions, which occur during sintering of obtained powders, have been characterized by X-ray diffraction (XRD) patterns, scanning electron microscope (SEM), differential thermal analysis (DTA), thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR) techniques. The mechanical properties of meleagris gallopova hydroxyapatite powders were determined by the measurements of density, hardness, porosity, activation energy for grain growth, variation of average grain sizes, fracture toughness and compression strength. The Fourier transform infrared spectra and the thermogravimetric analysis/differential thermal analysis thermograms of meleagris gallopova hydroxyapatite powders indicated that the presence of organic compounds were completely removed from the matrice. The X-ray diffraction patterns showed that decomposition of meleagris gallopova hydroxyapatite into tricalcium phosphate and calcium oxide was observed for the sintered samples at 1300 degrees C. At the same temperature, formation of microcracks were also detected by scanning electron microscopy image. Mechanical tests showed that maximum hardness, fracture toughness and compression strength values were measured for the sintered samples at 1200 degrees C.
Keywords: Meleagris gallopova; hydroxyapatite; sintering; GEL-DERIVED HYDROXYAPATITE; WET PRECIPITATION PROCESS; NATURAL HYDROXYAPATITE; HYDROTHERMAL SYNTHESIS; BOVINE HYDROXYAPATITE; TEMPERATURE; POWDERS; BONES; COMPOSITES; EXTRACTION